2022
DOI: 10.1029/2021gl096483
|View full text |Cite
|
Sign up to set email alerts
|

Are Significant Tornadoes Occurring Later in the Year in Southern Ontario?

Abstract: More than a dozen tornadoes occur on average every year in the Canadian province of Ontario (ECCC, 2017). While most are weak in nature (i.e., rated F/EF0-1), a number of tornadoes having far greater intensity have occurred. For example, F4 tornadoes in 1946For example, F4 tornadoes in , 1970For example, F4 tornadoes in and 1985 resulted in 31 deaths and hundreds of injuries.Though tornadoes in Ontario have been recorded March to December, the peak months are May to August. Over the last decade or more, Ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nonetheless, it is shown that Canadian Prairie strong tornadic storms are more dominated by thermodynamic and buoyant energy influences compared to larger wind shear influences in eastern regions. We suspect eastern Canada has stronger dynamics and winds at all levels partially due to more Spring and Autumn events that typically have well‐developed synoptic systems and over all less CAPE Future analysis will compare summer versus spring/autumn environments, since southern Ontario has been experiencing more late‐season events (Sills et al., 2022) and future cool‐season tornadoes may be stronger (Woods et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is shown that Canadian Prairie strong tornadic storms are more dominated by thermodynamic and buoyant energy influences compared to larger wind shear influences in eastern regions. We suspect eastern Canada has stronger dynamics and winds at all levels partially due to more Spring and Autumn events that typically have well‐developed synoptic systems and over all less CAPE Future analysis will compare summer versus spring/autumn environments, since southern Ontario has been experiencing more late‐season events (Sills et al., 2022) and future cool‐season tornadoes may be stronger (Woods et al., 2023).…”
Section: Discussionmentioning
confidence: 99%